Extent of Recreational Services Exploitation for Sustainable Local Development in Limbe, Cameroon - A., Baba; O., Toumba; N. N., Humphrey (International Journal of Global Sustainability, 2023)
The general tertiary sector consumption pattern in Limbe indicates the drive towards recreational services delivery for staggering urban development. Despite the evolution and benefits of recreational services as boosters to local socio-economic development, they do not have the attention they fully deserve resulting in severe environmental and socio-economic repercussions. This study seeks to examine the extent of recreational services exploitation for sustainable local development and the municipal responses in Limbe. A sample of 250 respondents was used to represent the entire population of the study area. In addition to interviews and field observations, secondary data from literature search was used to substantiate the arguments. Stratified random sampling technique was used to map out the appropriate recreational sites and services in Limbe. Data were analyzed using the Statistical Package for Social Science Standard (SPSS version 23.0) and presented in the form of tables, figures, maps and plates. Results reveal that Limbe has witnessed profound growth in recreational services in the last few decades due to its rapid population growth, private and government priorities and economic growth of the coastal area among others. Besides its major role in local socio-economic development, high congestion and taxes, poor maintenance among others have bedeviled its sustainable operations resulting in environmental degradation, congestion of waterways and insufficient economic and socio-cultural effects on the local populations. Therefore, there is the need for proactive management, optimization and transformation of recreational sites, proper sensitization, humanitarian advocacies, local participations in decision making process, increase investment, subsidies and employment to ensure sustained environmental quality, local socioeconomic growth and cultural responsibilities in the sector. Likewise, there should be adequate compliance to environment regulations and best practices for local socio-economic, environmental, and tourism management.